2006
DOI: 10.1103/physrevd.73.104014
|View full text |Cite
|
Sign up to set email alerts
|

Junction conditions in general relativity with spin sources

Abstract: The junction conditions for General Relativity in the presence of domain walls with intrinsic spin are derived in three and higher dimensions. A stress tensor and a spin current can be defined just by requiring the existence of a well defined volume element instead of an induced metric, so as to allow for generic torsion sources. In general, when the torsion is localized on the domain wall, it is necessary to relax the continuity of the tangential components of the vielbein. In fact it is found that the spin c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Likewise for the intersection of shells, without deficit angle [11] [12]. It has been shown that in some cases these results generalise to the first order formulation with non-vanishing torsion [13] [14].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Likewise for the intersection of shells, without deficit angle [11] [12]. It has been shown that in some cases these results generalise to the first order formulation with non-vanishing torsion [13] [14].…”
Section: Introductionmentioning
confidence: 87%
“…∂ takes into account orientations and is required to satisfy ∂∂ = 0. Relation (13) was introduced to guaranty that.…”
Section: B Cell Complexesmentioning
confidence: 99%
See 2 more Smart Citations